Bioactive components, physicochemical and starch characteristics of different parts of lotus (Nelumbo nucifera Gaertn.) plant: a review. (24th November 2020) - Showkat, Qazi A.; Rather, Jahangir A.; Abida Jabeen; Dar, B. N.; Makroo, H. A.; Majid, Darakshan
Summary: Lotus plant parts such as flower, seed, root, leaf and stem or rhizome have a great potential for food and non‐food applications. This review recognises the nutritional and therapeutic benefits, functional behaviour, post‐harvest processing and applications of the lotus plant. Its unique bioactive constituents, such as phenolic compounds, alkaloids, flavonoids and essential oils, have proven efficacy in improvement of health. The good amount of dietary fibre, starch, vitamins and minerals suggest that it has potentially an appropriate opportunity for future valorisation and application as functional additive and ingredient in the food industry. As a functional ingredient for use in the food industry like flour in bakery industry, as an antioxidant, for incorporation in baby foods, extruded products, beverages etc. there is a need to study the characteristics of lotus plant especially the rhizome part. Abstract : Lotus ( Nelumbo nucifera Gaertn .) Plant: A prelude of its current and potential applications.